Crizotinib may be effective for rheumatoid arthritis: a case report of a rheumatoid arthritis patient with lung cancer. Issue 2 (3rd July 2017) - Nakabo, Shuichiro; Gochi, Fumiaki; Yasuhara, Yumiko; Terada, Yasuji
Abstract: A 66-year-old woman with rheumatoid arthritis (RA) was seen in our outpatient rheumatology clinic. She had developed lung cancer at the age of 61, and received surgery and six courses of chemotherapy. However, the cancer recurred 2 years later and crizotinib (CRZ), which is an oral anticancer agent acting as an anaplastic lymphoma kinase (ALK) inhibitor, was started. Although her RA had been active before starting CRZ, it entered clinical remission. Her cancer was well controlled, but she sometimes stopped taking CRZ for several reasons. At these times, her RA symptom temporarily recurred. CRZ was continued for 1 year and 6 months, but finally switched to alectinib (ALC), which is another ALK inhibitor, because her cancer became resistant to CRZ. Interestingly, her RA became active after the switch, although both CRZ and ALC are ALK inhibitors. Since CRZ inhibits not only ALK but also MET, while ALC is a selective ALK inhibitor, MET inhibition was thought to be important in this case. This case suggests that CRZ can be a new therapeutic option for RA and MET is a promising treatment target.